(untitled) (Theatrum historiae, 2007)
Early modern society of Central Europe had to cope with being a neighbor to the Ottoman Empire, which represented a vastly different culture and/or civilization. The presence of “the other” was reflected on many different levels. The image of “the Turk” in print and contemporary propaganda in Bohemia and Moravia has already been studied, however, almost nothing is known about the reflection of the great eastern neighbor (and its threat) in material realm. This article, based upon the analysis of Turkish weaponry presented in aristocratic armories, holds out the question as to whether these collections could be dealt with as parts of the image of a nobleman – a successful and self-confident Christian warrior. The analysis is based upon 37 inventories of aristocratic armories in Bohemia and Moravia between 1560 and 1740, resulting in the formulation of the following thesis. During the period of the most imminent Ottoman threat, i.e. in the 16th century, there was little or no Turkish weaponry added to the armories of Bohemian and Moravian nobility. Even the noblemen who actively participated in the wars against the Turks and who were deeply interested in the conflict had no such needs. Presentation of onn’s military successes through the war trophies was limited to the court (archduke Ferdinand of Tyrol), where special propaganda and political goals were followed. Certain level of acquirement of Turkish weaponry starts only after the repulse of the Turks from Vienna in 1683, whereas this trend appears first in Moravia and only afterwards (probably because of geography) in Bohemia. A real boom of Turkish collections can be found as late as after 1720. However, there is no unifying principle, providing some clue to the process of their buying and presentation. Most of the studied owners were contented with a few items that (along with other exotic rarities from Muscovite, Tartar, Indian or Japanese production) were present in the armories primarily because of the contemporary taste and interest in Turkish culture. Usually there was no hidden message in their holding. Thus, if we exclude such rare exemptions as was the bishop of Olomouc (Olmütz), it seems that the question mark in the article’s title is more than appropriate. In its collections of weapons, aristocrats had little interest in presenting themselves as Christian knights who fought off and defeated the worst of all enemies.